Hra na klavír ve světle vědeckých poznatků - Rašková, Beata (Akademie múzických umění, Malostranské nám. 12, 118 00 Praha 1, http://www.amu.cz, 2018)
This thesis combines academic research and the knowledge of bodily functions and mental techniques with musical practice. As an introduction, it deals with the question of talent in general, as well as various factors affecting a musician’s success, diligence and appropriate motivation among them. The main body of the thesis focuses on the creative process and ways to induce creativity, concentrating on the effectiveness of practice and its specific characteristics: the most suitable time of the day, the optimal length of practice, goal planning and individual techniques. This section is accompanied by an overview of the most frequent mistakes made while memorising compositions and a description of the mental process of committing information to long-term memory, including the most effective learning techniques. Finally, the thesis examines the issue of mental preparation for public performances and discusses long-term as well as short-term preparation techniques, considering the question of lifestyle and dietary recommendations before and after a concert.
Keywords: hra na klavír; cvičení